The Role of Lean Management in Enhancing Job Performance: An Applied Study on the Ministry of Health in the Kingdom of Saudi Arabia - Al-Otaibi, Muneera Musallat Fahad (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to identify the role of lean management in raising job performance in the Ministry of Health in the Kingdom of Saudi Arabia. Where a simple random sample of (514) individuals was studied, and the results of the research concluded a set of main results, including: The level of lean management practice and the level of job performance in the Ministry of Health in the Kingdom of Saudi Arabia came with a high degree, And that lean management with its dimensions (continuous improvement, work organization, standard work, six-way deviation) has a positive impact on raising job performance, as the effect rate reached 79.6%, except for the dimension (multifunctional employees) that has no effect on raising job performance in the Ministry of Health in Kingdom of Saudi Arabia, The study recommended the need to pay attention to lean management tools and expand their application. Because of its impact on finding radical solutions that reduce waste in the organization, it also recommended work to reduce pressure on employees, encourage innovation and generate successful ideas for work development.
Keywords: lean management; job performance; continuous improvement; work organization; standard work; hexagonal diffraction; multifunctional employee